Data in support of the comparative genome analysis of Lysinibacillus B1-CDA, a bacterium that accumulates arsenics - Rahman, Aminur (Data Brief, 2015)
This study is a part of our long term project on bioremediation of toxic metals and other pollutants for protection of human health and the environment from severe contamination. The information and results presented in this data article are based on both in vitro and in silico experiments. in vitro experiments were used to investigate the presence of arsenic responsive genes in a bacterial strain B1-CDA that is highly resistant to arsenics. However, in silico studies were used to annotate the function of the metal responsive genes. By using this combined study consisting of in vitro and in silico experiments we have identified and characterized specific genes from B1-CDA that can be used as a potential tool for removal of arsenics as well as other heavy metals from the contaminated environment.